2 - Les nouvelles relations Est-Ouest et leurs incidences sur la coopération CEE-ACP: by Blaise Sary Ngoy - Blaise Sary Ngoy, (Africa Development, 1993)
Is the Single European Act which led to closer relations between E ex-COMECON countries enough reason to justify the marginalization o countries? The comparative structure of exchanges, financial and techn assistance and investments do not encourage a positive response. The compet between the East and ACP countries in the common market covers an insigni part only of ACP agricultural exports to the EEC countries except minera petro-chemicals. EEC financial assistance to ACP countries is on a contrac and is carried out through ED F whereas for the East it is EBRD anď EIB wh in charge. The marginalization hypothesis can be verified through a look at b aid, even if some EEC countries still privatize it. Direct investments are orie towards petro-chemicals, energy and services and involve USA and the Industrial Policy. The loosening of EEC I ACP relations is not due to the tighten the relations between the EEC and the East. The reasons for such a decrease be found in the production structures, the inappropriate management a increasing political uncertainties in the South.